Merry Christmas, Alex Cross [large type] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2012)
It's Christmas Eve and Detective Alex Cross is called away from his family to resolve a horrific hostage situation that is spiraling out of control.